Implentasi Manajemen Mutu Pembelajaran Di Mts Swasta Al- Wasliyah Tembung - Amiruddin Siahaan, Rahmad Hidayat, Ahmad Sulaiman, Muhammad Yunus (Cybernetics: Journal Educational Research and Social Studies, 2021)
The purpose of good quality learning in cognitive, effective and psychomotor aspects requires a change in the paradigm in learning that was originally centered on the teacher, switched to students, in a method that was originally dominated by teacher exposure replaced by student participation, and in the approach initially the text turned into contextual. This requires a planning, implementation and assessment and follow-up of learning outcomes so that the learning process in the classroom has quality. The research conducted is qualitative. The result of the research is that the learning planning in the private MTS Al-Wasliyah Tembung has been carried out well, this is because the learning planning that is applied is in accordance with the indicators in Rusman's theory that the researcher uses. However, there are also those who have not used teaching aids and learning methods: a) Preliminary Activities, b) Core Activities, c) Closing Activities